2018
DOI: 10.1177/0730888417753048
|View full text |Cite
|
Sign up to set email alerts
|

Social Structure and the Paradox of the Contented Female Worker: How Occupational Gender Segregation Biases Justice Perceptions of Wages

Abstract: This article provides a structural explanation for the paradox of the contented female worker. Although they are generally aware that they earn less than men, women usually perceive their wages as more just. This article argues that men and women do not differ in how they perceive their wages, yet the gendered segregation of the labor market will constrain the availability of preferred same-gender referent standards in some occupations. Random- and fixed-effects analyses of longitudinal data of the German Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…In reflexive justice evaluations, people evaluate their own rewards (observer = recipient); in non-reflexive justice evaluations, people evaluate the rewards of others (observer = recipient). Previous studies on reflexive justice find a gap between the evaluations of men and women, with men expecting higher wages than women (Liebig et al, 2011(Liebig et al, , 2012Valet, 2018). However, reflexive justice judgments are based on individuals' own outcomes and are therefore driven by two forces, justice deliberations and self-interest (Younts and Mueller, 2001).…”
Section: The Justice Evaluation Processmentioning
confidence: 99%
“…In reflexive justice evaluations, people evaluate their own rewards (observer = recipient); in non-reflexive justice evaluations, people evaluate the rewards of others (observer = recipient). Previous studies on reflexive justice find a gap between the evaluations of men and women, with men expecting higher wages than women (Liebig et al, 2011(Liebig et al, , 2012Valet, 2018). However, reflexive justice judgments are based on individuals' own outcomes and are therefore driven by two forces, justice deliberations and self-interest (Younts and Mueller, 2001).…”
Section: The Justice Evaluation Processmentioning
confidence: 99%
“…Another area worth investigating is what is termed, "the paradox of the contented female worker". 24,25 This paradox is the finding that although a woman may know that she is paid less than men are, she may not feel entitled to more pay. 24 Recently Valet 25 demonstrated that the paradox is not present when women are in male-dominated careers.…”
Section: Limitationsmentioning
confidence: 99%
“…24,25 This paradox is the finding that although a woman may know that she is paid less than men are, she may not feel entitled to more pay. 24 Recently Valet 25 demonstrated that the paradox is not present when women are in male-dominated careers. Future studies with students may first ask students their perceptions of the gender make-up for certain positions and then ask their expected starting salaries.…”
Section: Limitationsmentioning
confidence: 99%
“…Sociologists, conversely, have focussed upon the greater incidence of the paradox amongst lower paid employees. Women, it is argued, tend to choose other women as pay 'referents' and additionally, structural disadvantage and gendered occupational segregation encourage women to compare their pay to other similarly low paid women (Loscocco and Spitze;1991;Valet, 2018).…”
Section: The Limitations Of Previous Explanationsmentioning
confidence: 99%
“…For more than thirty years 'paradoxical' patterns in the pay satisfaction of men and women have been observed. Evidence suggests that women are often equally or more satisfied with their pay than men (Buchanan, 2005;Smith 2009;Valet, 2018). This 'paradox' occurs in spite of the fact that, on average, women tend to receive lower pay than men.…”
Section: Introductionmentioning
confidence: 99%